PENGEMBANGAN SISTEM BERBASIS WEB UNTUK DIGITALISASI ADMINISTRASI PELAYANAN SURAT DI DESA RIAS - Rizqi Pratama (KHARISMA Tech, 2026)
Village administration plays a crucial role in the implementation of governance at the village level. However, in Rias Village, Toboali District, administrative processes are still carried out manually, which hinders service efficiency, increases the likelihood of recording errors, and limits public access to important documents. To address these issues, a web-based administrative information system was developed to digitalize the village’s correspondence services. Through this system, residents can submit requests for official letters online, which are then verified and processed by the village operator. The system also provides a notification feature for tracking submission status. Additionally, it supports digital document downloads, user account management by the admin, administrative letter type management, and an archiving feature accessible to both admin and operator. The system was developed using the Rapid Application Development (RAD) method. The results of the User Acceptance Testing (UAT) achieved a score of 91.42%, categorized as “Highly Feasible.” The implementation of this system has made administrative processes in Rias Village more efficient, transparent, and easily accessible without requiring direct visits to the village office.